ANALISIS PENGARUH BOOK TO MARKET, SIZE, SYSTEMATIC RISK, DAN MOMENTUM TERHADAP RETURN SAHAM SMALL BUT LIQUID DAN BIG BUT ILLIQUID (Studi pada Perusahaan yang terdaftar di Kompas100 Tahun 2011-2015) - Ulfah, Firda Huwaida; Arfianto, Erman Denny (Diponegoro Journal of Management, 2017)
The research developed the factors that affect in stock returns. One of the "missing factor" that developed  the stocks that have small capitalization value with high frequency. This type of behavior has not expected oftenly. The purpose of this study is to analyze the influence of book to market, size, systematic risk,and momentum on stock returns in small but liquid and big but illiquid studies on companies KOMPAS100 2011-2015.The population in this study is a company with small but liquid stock category and big but illiquid stock category sorted by method purposive sampling to obtain these categories which has a number of 100 samples, of which 50 categories of samples small but liquid and 50 samples withcategory bigbut illiquid which annually features 10 different samples in accordance with these criteria.Research results in the category of small but liquid, book to market a significant negative effect on returns, stock size negative and not significant to return, stock systematic risk positive effect and no significant effect on returns, stock  and the momentum positive and significant impact on returns. stock  While the research results in the category of big but illiquid, book to market negative and not significant to return, stock size has a positive effect and no significant effect on returns, stock systematic risk significant negative effect on returns, stock  and the momentum positive and significant impact on returns stockDifferent test showed that the difference in returns small but liquid and big but illiquid evaluation in the first year after the establishment has a significance value of 0.008 and the value of T count greater than T table as worth 2.02269 is 2,790, which means there are significant differences. While evaluating the second and third years after the establishment did not have a significant difference in the presence of evidence that the evaluation of the second year of significant value amounted to 0,544 and evaluations in the third year has a significance value of 0.626 which means the absence of a significant difference